DESAIN KURIKULUM BERORIENTASI PADA NILAI ADAT, BUDAYA DALAM MEMBENTUK KARAKTER PESERTA DIDIK HADAPI ERA SOCIETY 5.0 - Mukhtar Mukhtar (STAI Sangatta Kutai Timur, 2021)
The presence of the idea of the era of society 5.0 makes the world, including Indonesia, have to work hard to face this shift. His quick arrival offers hope and convenience for the future of mankind. However, behind the offer, the erosion of the character of students is also a concern in the world of education. The curriculum at educational institutions is currently not effective enough to strengthen character. This paper tries to explore and offer a curriculum design that is oriented to the customs and culture of the community which is formulated on the development of information technology in character building. This study is a literature study, the primary data sources in this study are books and journals related to the era of society 5.0 and its impact on character. Secondary data is news/information from various media and the internet that are relevant to the research topic. The data obtained is then interpreted using descriptive analysis to get conclusions using the inductive deductive method. The results of the study show that the era of society 5.0 has an impact on character erosion, for that it is necessary to strengthen character through curriculum design which includes the formulation of a mission-based on traditional and cultural values, assessment of learning needs before the education process, setting curriculum goals based on character strengthening, using digital-based educational strategies, and strengthening educators with an understanding of traditional and cultural values and the ability to innovate learning media.